How Feasible Is a Convertible Ijarah Contract for SME Financing?: A Simulation Approach - Zuliani Dalimunthe; Akhmad Syakhroza; Mustafa E. Nasution; Zaafri A. Husodo (Journal of Islamic Monetary Economics and Finance, 2019)
Islamic financial institutions have relied for decades on margin-based contracts to provide financing for the business sector, despite the basic idea that Islamic finance is expected to provide an equity-based or a profit and loss sharing (PLS) contract. This fact raises the need to encourage the use of a margin-based instrument with an innovative scheme that allows for conversion of the contract into a PLS-based contract. Moreover, we propose a convertible ijarah contract to fill this need. A convertible ijarah contract is an ijarah (rent) contract that is convertible to a PLS contract according to the Islamic financier’s decision. In this study, we simulate three scenarios of project financing with (a) murabaha as a margin-based contract, (b) musharaka as a PLS contract and (c) a convertible ijarah contract. The aim is to evaluate whether the convertible ijarah contract will provide a higher return for the financier compared to the other contracts. The main input of the simulation is nine sectors of Indonesian SMEs’ financial performance. We found that when the financial performance of Indonesian SMEs was measured by short-term financial performance, the convertible ijarah contract outperformed the murabaha contract for all sectors but did not outperform the musharaka contract, except for low-margin sectors. However, when the financial performance of Indonesians SMEs was measured by long-term economic performance, we found that the convertible ijarah contract outperformed the murabaha contract and musharaka contract for almost all sectors.